Bladder Dysfunction and Vesicoureteral Reflux - Ulla Sillén (Advances in Urology)
In this overview the influence of functional bladder disturbances and of its treatment on the resolution of vesicoureteral reflux (VUR) in children is discussed. Historically both bladder dysfunction entities, the overactive bladder (OAB) and the dysfunctional voiding (DV), have been described in conjunction with VUR. Treatment of the dysfunction was also considered to influence spontaneous resolution in a positive way. During the last decades, however, papers have been published which could not support these results. Regarding the OAB, a prospective study with treatment of the bladder overactivity with anticholinergics, did not influence spontaneous resolution rate in children with a dysfunction including also the voiding phase, DV and DES (dysfunctional elimination syndrome), most studies indicate a negative influence on the resolution rate of VUR in children, both before and after the age for bladder control, both with and without treatment. However, a couple of uncontrolled studies indicate that there is a high short-term resolution rate after treatment with flow biofeedback. It should be emphasized that the voiding phase dysfunctions (DV and DES) are more severe than the genuine filling phase dysfunction (OAB), with an increased frequency of UTI and renal damage in the former groups. To be able to answer the question if treatment of bladder dysfunction influence the resolution rate of VUR in children, randomized controlled studies must be performed.